Analisis Yuridis terkait Peran Tni sebagai Pertahanan dan Bela Negara dalam Menghadapi Organisasi Papua Merdeka (OPM) - Nur Pratama, Daya; Safira, Ishma; Wicaksono Adi, Satrio; Triadi, Irwan (CV. Era Digital Nusantara, 2024)
This journal writing discusses the role of the TNI as Indonesia's front guard and defense in facing the Free Papua Organization (OPM) which has occurred since pre-reformation, post-reformation, and even now based on the laws and regulations in force in Indonesia. Indonesia. This research method uses methods. This writing method uses a literature approach which takes as its basis the laws and regulations in force in Indonesia and uses a descriptive analysis method, namely by analyzing existing problems and the role of the Indonesian National Army as the main force of defense and national security. The role of the Indonesian National Army (TNI) as the front guard and defense of the country in facing other acts of terrorism from the Free Papua Organization (OPM) is emphasized in Law no. 34 of 2004 concerning the Indonesian National Army in chapter VI concerning the deployment and use of TNI forces. The TNI as a component of national defense and national defense is correct in implementing existing regulations in Indonesia. However, acts of terrorism that are still occurring today must be used as evaluation material to further refine military strategies in this case so that the OPM conflict can be resolved quickly.